Cloud-Based NAS (Network Attached Storage) Analysis as an Infrastructure as A Service (IAAS) Using Open Source NAS4FREE and Owncloud - Hariyo Sasongko; T Yudi Hadiwandra (IT Journal Research and Development, 2022)
At this time, computer systems and networks are an essential part of human life. The number can see this of computer users in the office or on campus, and at school. This need has reached a relatively large number. To access data, many computer users in the network continue to increase, impacting the selection of servers, and large data storage media is necessary. Currently, the storage media that is often used to store data still uses physical media such as hard disks, flash disks that are virus-prone and easy to lose. Another problem also arises when physical storage has a relatively high price compared to cloud storage that can be accessed anywhere when needed.